Comprehensive review of myocardial injury after noncardiac surgery: prevention, intervention, and long-term management strategies - Moiud Mohyeldin; Sarah J. Norman; Ayzia Carney; Courtney Odza (Journal of Cardiothoracic Surgery)
Abstract Myocardial Injury after Noncardiac Surgery (MINS) is an increasingly recognized complication that significantly impacts postoperative morbidity and mortality. Characterized by elevated cardiac troponin levels without overt ischemic symptoms, MINS presents a challenge in perioperative care. This review article explores the epidemiology, etiology, and management of MINS, with a particular focus on prevention and the latest management strategies. We discuss the role of aspirin, statins, anticoagulation, and Dual Antiplatelet Therapy (DAPT) within the context of MINS, drawing on evidence from notable clinical trials as well as observational studies. Despite advancements in understanding and managing MINS, the condition continues to be associated with high mortality and major adverse cardiovascular events (MACE), underscoring the need for ongoing research and development of more effective management protocols.